The Effects of Service Quality, Experience, Consumer Satisfaction, and Brand Switching Behavior (Case Study of Karadenta Care) - M. Rafid; Andriya Risdwiyanto; Kraugusteeliana Kraugusteeliana; Geofakta Razali (BADAN PENERBIT STIEPARI PRESS, 2023)
Research at the Karadenta care clinicit aims to analyze the effect of service quality, consumer experience and variation-seeking behavior on brand switching. Consumer satisfaction is then used as mediation of consumer experience and service quality on brand switching. This study used a purposive sampling technique with a total of 82 respondents who were beauty clinic patients who had changed services from the previous beauty clinic and were currently using beauty treatments for 1 year at the current beauty clinic. Questionnaire data were processed using Partial Least Square (PLS) analysis with testing measurement model (outer) model and inner model with path coefficients. The results of the analysis show that service quality and customer experience have a significant effect on customer satisfaction. The variable of consumer satisfaction has a negative effect on variation seeking behavior and variation seeking behavior has a positive effect on brand switching, but consumer satisfaction has no effect on brand switching. The consumer satisfaction variable does not mediate service quality and consumer experience towards the switching of the Karadenta care brand.